John Marchmont's Legacy, Volume 1 (of 3) - Braddon, M. E. (Mary Elizabeth), 1835-1915 (Salt Lake City, UT : Project Gutenberg, 2010)
"John Marchmont's Legacy, Volume 1 (of 3)" by M. E. Braddon is a novel written in the mid-19th century. The narrative follows the life of Edward Arundel, a young man whose fate becomes intertwined with that of his former mathematics tutor, John Marchmont, and Marchmont's daughter, Mary, as they navigate the complexities of social status, inheritance, and personal struggles against the backdrop of Victorian society. The story hints at themes of friendship, loyalty, and the pursuit of happiness amidst adversity. The opening of the book introduces Edward Arundel, who encounters John Marchmont, the once-promising tutor now reduced to a lowly stage supernumerary due to poor health. As the two reconnect, John reveals his fears for the future of his daughter, Mary, should he pass away before inheriting a sizable fortune tied to the death of several family members. He entrusts Edward with the future protection of Mary, who showcases both precocious maturity and a childlike innocence. Through their interactions, the reader begins to see the depth of their bond, setting the stage for a rich exploration of the characters and their intertwined destinies in subsequent chapters. (This is an automatically generated summary.)
Release date is 2010-12-01
Produced by Clare Graham, using scans from the Internet Archive
Keywords: Triangles (Interpersonal relations) -- Fiction; Children of clergy -- Fiction; Lincolnshire (England) -- Fiction; Women intellectuals -- Fiction